PEMANFAATAN TEKNIK WEB SCRAPING PYTHON UNTUK SISTEM PENCARIAN PRODUK DI TOKO ONLINE - Adi Sopian; Andy Dharmalau; Alpindo Alpindo (Institut Teknologi dan Bisnis Swadharma, 2022)
Sales and purchase transactions utilizing electronic systems with the internet through computer networks has grown rapidly. Buying goods in online stores sometimes the items you are looking for are not what you want, especially in price and item details, it can even happen that the item you are looking for is not found. In searching for goods using search engines such as google, yahoo, it will generate information on goods in the form of a list of website addresses. So that the information obtained is not as desired, people have to visit the online shop address one by one, causing people to waste a lot of time. The results of the research on the product search system using web scraping techniques to several e-commerce, namely tokopedia, shopee, elevania and blibli, have succeeded in obtaining data in the form of product names, number of stock items, url, rating and product images. So that people can easily find the desired item along with the data